The Muslim question and Russian imperial governance - Campbell, Elena I. (Indiana-Michigan series in Russian and East European studies., 2015)
From the time of the Crimean War through the fall of the Tsar, the question of what to do about the Russian empire's large Muslim population was a highly contested issue among educated Russians both inside and outside the government. As formulated in the 19th and early 20th centuries, the Muslim Question comprised a complex set of ideas and concerns that centered on the problems of reimagining and governing the tremendously diverse Russian empire in the face of the challenges presented by the modernizing world. Basing her analysis on extensive research in archival and primary sources, Elena I.